AI Transforms Ecommerce Management and Regulation in Uzbekistan: AI Mengubah Manajemen dan Regulasi E-niaga di Uzbekistan - Yashnarovna, Isokhujaeva Munira (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the integration of artificial intelligence (AI) into Uzbekistan's e-commerce sector, aiming to enhance business management, develop new models, and increase governmental regulatory effectiveness. By employing mathematical models based on a knowledge base and product logic principles, the research predicts and facilitates alternative management decisions, improving market monitoring and administrative procedures. The findings reveal that AI significantly enhances decision-making quality and regulatory efficiency, suggesting its potential as a cornerstone for modern e-commerce management strategies. This contributes to the advancement of the digital economy and the improvement of business and consumer conditions in Uzbekistan. Highlights: AI Integration: Enhances decision-making and administrative procedures in Uzbekistan's e-commerce sector. Mathematical Models: Uses knowledge bases and product logic to improve market monitoring and management decisions. Economic Impact: Contributes to the development of the digital economy, benefiting businesses and consumers. Keywords: Public Administration, E-commerce, Digital Economy, Artificial Intelligence, Regulatory Efficiency